Study Kasus Deformasi Plastis - Nono, Nono; Yamin, R. Anwar (Department of Civil Engineering, Diponegoro University, 2005)
In genelar, defect in the flexible pavement on road links which heavy loaded traffic and have high temperature is plastic deformation. This paper discusses some causes of plastic deformation occurred in the field and some factors that effect occurring plastic deformation. Plastic deformation found in the field is effect of bad design gradation and of high bitumen content as caused mix design without void in mix at refusal density. Plastic deformation with rut depth is less than 20 mm, displacement or shear occurred on the wearing course (ACWC). In spite of rut depth is more than 20 mm, displacement or shear also occurred on the second layer or binder course (ACBC). Base on rut depth above, so we can used as a guide for determining of asphalt layer is should be scraped or repaired. Giving attention for example to consider void in mix at refusal density on mix design and the uses of asphalt mixtures which relatively high stiffness can reduce plastic deformation.Keywords: flexible pavement, plastic deformationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3896[How to cite: Nono dan Yamin, R.A., 2005, Study Kasus Deformasi Plastis, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 48-59]